Bike lanes’ impacts on bike sharing system usage: From citywide to road-specific exploration of bike trips - Jie-Yu Li; Pi-Cheng Chen (Journal of Urban Mobility)
Bike lane construction, a promising sustainable transport strategy, has the potential to significantly increase ridership and reduce the reliance on private vehicles in cities. While many studies analyze citywide statistical trends, few explore the effects of different bike lanes and examine the nuanced impacts of lane-specific designs and configurations. This study aims to provide an applicable approach for other future studies to analyze local situations in different cities. So, this study addresses that gap by using both one citywide and three road-specific analyses to evaluate six bike lanes in Taipei City. The findings reveal that three lanes exhibited significant post-construction trip increases, while the remaining three did not. The findings also reveal that bike trips on longer and wider lanes may demonstrate substantial increases in ridership compared to shorter or shared lanes. This study also discusses the other critical role of lane characteristics, such as separation from pedestrian pathways, the alignment with metro stations, and higher station density, which could contribute more significantly to ridership growth in Taipei. These insights underscore the importance of tailored infrastructure planning in optimizing bike-sharing systems. By analyzing trip data spanning 2013–2018 with innovative spatial methodologies, this research not only highlights the effectiveness of road-specific evaluation but also informs sustainable urban planning strategies to achieve progress toward the United Nations’ Sustainable Development Goal 11.